-5a+7+4a=-(a+7)

Simple and best practice solution for -5a+7+4a=-(a+7) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5a+7+4a=-(a+7) equation:


Simplifying
-5a + 7 + 4a = -1(a + 7)

Reorder the terms:
7 + -5a + 4a = -1(a + 7)

Combine like terms: -5a + 4a = -1a
7 + -1a = -1(a + 7)

Reorder the terms:
7 + -1a = -1(7 + a)
7 + -1a = (7 * -1 + a * -1)
7 + -1a = (-7 + -1a)

Add 'a' to each side of the equation.
7 + -1a + a = -7 + -1a + a

Combine like terms: -1a + a = 0
7 + 0 = -7 + -1a + a
7 = -7 + -1a + a

Combine like terms: -1a + a = 0
7 = -7 + 0
7 = -7

Solving
7 = -7

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| F(x)=2(x^2-9x+5)-5(x-k) | | n+40=41 | | -5a-7+4a=-(a+7) | | 6x-5=x^2+4 | | Y=sqrt(x-4)+5 | | 2x+3x=1000 | | 2x+80=152 | | n+12=13n | | x=4509307201 | | -7x=-154 | | n+8-n=9n-n | | 5a+7-4a=-(a+7) | | 5+-1v+4v=1+5v+3 | | n+8=9n | | -5a+7-4a=-(a+7) | | -3x^2-10x+5=0 | | 6x=-14x | | -105+8x+6x^2+x^3=0 | | 4x^2+8x=38-6y^2 | | 2xy*3-60+x=6xy*10 | | -(-15x)-3= | | xy=3x^2-6+y | | 9x+4x-6x-5=2 | | 108=12X^2 | | 3x+5x-6x-5=5 | | mx+4=3x-n | | 2x+9x-7x-5= | | p-8=24 | | e^5x+6=8e^3x | | 4sin^4x-1=0 | | 7(8x+2y)= | | 16=s+7 |

Equations solver categories